Australian University Transnational Education Programs: An Empirical Investigation of the Business Models - Lim, Sen Lee (Curtin University, 2019)
This in-depth qualitative case study explores the criteria two Australian public universities use in the selection between the Direct (DM) and Outsourced Models (OM) of TNE business delivery, and the role of the theories of the firm viz., transaction cost economics (TCE), property rights theory (PRT) and agency theory (AT) in driving these criteria and the longevity of the models. It identified significant tipping points along the TNE journeys of each university, and four new models of TNE delivery.